2008
DOI: 10.1111/j.1365-3180.2008.00621.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Moroccan populations of Orobanche foetida: evolving from parasitising wild hosts to crop plants

Abstract: Summary Orobanche foetida is widely distributed in western Mediterranean countries infecting wild legumes. Recently it has been reported in Morocco infecting common vetch, presenting a further constraint for legume production in this area. Comparative studies between Orobanche populations attacking wild species and Orobanche populations growing on crops from the same region may help to clarify whether a host specialisation process occurred. In the present study, the genetic variability of five O. foetida popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 29 publications
1
43
0
Order By: Relevance
“…foetida confirming the lack of infection ever observed in the faba bean in the field (Pujadas-Salvá, 2002; Rubiales et al, 2005; Vaz Patto et al, 2008). Some P. ramosa infection could occur, but at low levels.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…foetida confirming the lack of infection ever observed in the faba bean in the field (Pujadas-Salvá, 2002; Rubiales et al, 2005; Vaz Patto et al, 2008). Some P. ramosa infection could occur, but at low levels.…”
Section: Resultssupporting
confidence: 78%
“…foetida and var. lusitanica are widely distributed in natural habitats in the Western Mediterranean area parasitizing wild herbaceous leguminous plants belonging to the genera Anthyllis, Astragalus, Ebenus, Lotus, Medicago , and Trifolium but not legume crops (Pujadas-Salvá, 2002; Vaz Patto et al, 2008). P. aegyptiaca is a very damaging species on vegetable crops prevalent in the Eastern Mediterranean and Near East that can also affect faba bean (Parker, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Based on AFLP (amplified fragment length polymorphism) markers, this genetically diverse outcrossing weed does not show genetic differentiation correlated with host specificity, but rather, it is correlated with geography (Welsh and Mohamed, 2011), suggesting that the weed is a generalist that can easily invade new crop hosts. Similarly, no genetic differentiation based on AFLP has been found between populations of broomrape (Orobanche foetida) infesting wild legumes and a population parasitizing cultivated vetch, suggesting a generalist ability to undergo host shifts onto cultivated species (Vaz Patto et al, 2008). Blackgrass (Alopecurus myosuroides), a non-parasitic weedy grass common in cereal fields worldwide, has high genetic diversity based on amplified fragment length polymorphisms within the populations, and little divergence between populations collected across Europe (Menchari et al, 2007).…”
Section: The Origins Of Agricultural Weedsmentioning
confidence: 99%
“…Vaz-Patto et al (2008) studied O. foetida populations with AFLP markers and reported that 13.7% of the genetic variability was among populations and 86.3% of the genetic variability was within populations. Variability and gene flow in Orobanche species attacking crops is probably related not only to their mating systems, but also reflect human intervention in distributing species from one region to another (Román et al 2007).…”
mentioning
confidence: 99%